Estádio de Desenvolvimento do Milho. 1. Efeito sobre a Produção, Composição da Planta e Qualidade da Silagem - Lavezzo, W.; Lavezzo, OENM; Neto, O. C. (Revista Sociedade Brasileira Zootecnia, 1997)
The objective of this study was to evaluate the influence of maturity on the production, stalk/leaf/ear relationship, chemical composition, and quality of corn silage (Zen mays, L.). Four harvests were made from the early milk (23.49% DM) to the semi-hard dough stage. (30.70%DM). After these evaluations, the corn was ensiled in 200 liter metal drums. After six months of storage, the quality of the silages was determined. The corn dry matter production was higher at the dough and semi-hard dough stages (9866 and 9896 t/ha, respectively) than in the early milk stage (7460 t/ha). The ears with the maturity showed a increase in dry matter (20.93 to 43.51%), acid detergent fiber decrease (32.46 to 18.62%), and maintainance of the crude protein content (average = 8.27%). The stalks and leaves decreased from 33.31 to 27.18% and from 34.17 to 23.66%, respectively, while the ears increased from 32.52 to 49.16% from the early milk to the semi-hard dough stages. All experimental silages attained good quality, independent of corn development stages. The corn can be ensiled from the early milk and soft dough stages without a decrease in silage quality, but the restricting factor under those conditions was a lower dry matter content (24.35 and 28.65%, respectively).
Stage of corn development .1. Effect on plant production, composition, and quality of the silage
Keywords: chemical composition; corn; production; silage quality